ANALISIS PENGARUH KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA BENGKEL PERJAKA MOTOR KABUPATEN KEDIRI - Nandalesti, Mardiana (Universitas Nusantara PGRI Kediri, 2022)
The author analyzes the effect of service quality variables, price variables, location variables on customer satisfaction variables at the Perjaka Motor Workshop in Kediri Regency. The author uses a sample of 40 people who use criteria that have been confirmed by the method used is Incidental Sampling, so that this research approach the author uses quantitative. An analytical technique in this study the author uses multiple linear regression with hypothesis test points with SPSS version 23 tools. In this study the authors suggest (1) service quality does not affect customer satisfaction variables, (2) price variables have an influence on customer satisfaction , (3) location which has no effect on customer satisfaction variable, (4) service quality variable, price variable, location variable together/simultaneously have an influence on customer satisfaction variable at Perjaka Motor Workshop in Kediri Regency